EKSPLORASI MEDIA PEMBELAJARAN DALAM MENINGKATKAN KETERAMPILAN MENULIS DI SDN SAROKA 1 - Misriyani; Misbahudholam AR, Muhammad; Puji Astuti, Yeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the use of learning media to improve students' writing skills at Saroka 1 Elementary School. Using qualitative research methods, data were collected through observation, interviews, and questionnaires. The results indicate that the use of varied learning media, such as videos, images, and interactive applications, has a positive effect on students' motivation and writing skills. Students' responses to the media used also tended to be positive, indicating an increase in their interest and writing output. Based on the students' responses to the use of learning media for writing skills, it was found that all students (100%) said they were interested and agreed that the learning media could help improve their understanding of the material presented by the teacher. This finding shows that the writing skills media can capture students' attention while also supporting the learning process more effectively.